Experiencias de aprendizaje en el desarrollo cognitivo de los niños de 2 a 3 años del centro de desarrollo infantil 8 de diciembre ubicado en la ciudad de Loja, periodo 2019-2020. - Gordillo Armijos, Josselyn Michelle (2021)
The present investigation: LEARNING EXPERIENCES IN THE COGNITIVE DEVELOPMENT OF CHILDREN FROM 2 TO 3 YEARS OLD FROM THE CENTER FOR CHILD DEVELOPMENT 8 DECEMBER LOCATED IN THE CITY OF LOJA, IN THE PERIOD 2019-2020; the general objective was: To analyze the importance of learning experiences in the cognitive development of children. The investigation had a non- experimental design, because the context under investigation wasn't manipulated or experienced. To develop the study, the following methods were used: descriptive, analytical- synthetic, inductive and deductive. The instruments that were part of the information collection were: the brief, observation and the Bayley scale of Child Development. The research arose from a research project proposed by the Initial Education career, where a common diagnostic was made in 11 municipal child development centers in the city, with a total of 353 child between 2 and 3 years, with a sample made up by 4 teachers and 7 children. The most relevant results showed that 100% of the children had a limited cognitive development index, and 72% of them did not have the appropriate motor characteristics for their age. Therefore, it's concluded that it's necessary to apply learning experiences as a didactic tool to enhance the cognitive development of children, that through stimulating experiences acquire the ability to function fully according to their age.